Pemanfaatan Hasil Pertanian Dalam Pembuatan Lilin Aromateraphy Kopi Di Desa IV Suku Menanti - Pingki, Anadiya; Yanuarti, Mira; Prisdinawati, Dwita; Mulyani, Resy (-, 2025)
Coffee is one of the world's agricultural commodities that has been cultivated in more than 50 countries. Coffee is a drink made from brewed coffee beans that have been roasted and ground into powder. There are two varieties of coffee trees that are generally known, namely Robusta Coffee (Coffea canephora) and Arabica Coffee (Coffea arabica). Coffee is a very famous commodity in Indonesia. In addition to having entered Indonesia since the Dutch colonial era, coffee is also famous for its taste and aroma. Coffee is a superior potential in several regions in Indonesia, one of which is in Village IV Suku Menanti, Sidang Dataran District, Rejang Lebong. However, the utilization of coffee agricultural products as a superior village commodity has not been optimally implemented. People only sell coffee beans through certain marketing channels. In fact, coffee can also be processed into a product, one of which is coffee aromatherapy candles. Candles are a source of light consisting of a wick covered with solid fuel that is flammable. Before the 19th century, the fuel used was usually beef fat (which contains a lot of stearic acid). Aromatherapy is a method of treatment using volatile plant aromas. Natural aromatherapy candles are certainly better than synthetic fragrances because they can interfere with the health of those who inhale them. Coffee aromatherapy candles are aromatherapy candles with natural fragrance ingredients, namely coffee. By utilizing agricultural products, farmers can empower existing resources as an effort to increase body immunity through coffee aromatherapy candles and can improve the economy of the IV Suku Menanti Village community.